Why do home-owners do better? - Dockery, Michael; Bawa, Sherry (2019)
Australians who own their own home display favourable outcomes on a range of socio-economic indicators when compared to renters, and substantial benefits of home-ownership also appear to accrue to their children. Whether such effects are causal or simply reflect pre-existing characteristics associated with selection into home-ownership has important implications for decisions to be made by individuals and families, and for policy in light of recent declines in home-ownership rates for younger adults. The literature primarily attributes the better outcomes of those in home-ownership to greater residential stability, particularly in the case of children’s educational attainment, and a greater incentive to invest in the local community, but there is little empirical evidence on the sources of benefits from home-ownership in Australia. Using longitudinal data from the Household, Income and Labour Dynamics in Australia survey (HILDA) this paper employs a range of strategies to test competing hypotheses relating to causal mechanisms and selection effects associated with home-ownership. We focus on indicators of physical and mental health, life satisfaction and, for youth, educational attainment. The results suggest the better physical and mental health outcomes of home-owners reflect selection effects rather than any causal impact of home-ownership on health. However, there is evidence that home-ownership promotes higher life-satisfaction, and of residential stability and parental community engagement associated with parental home-ownership impacting beneficially on outcomes for youth.